Mantrailing as a form of physical recreation in Poland: Mantrailing as a form of physical recreation in Poland - Warcholik, Witold; Chmielowska, Dorota (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2021)
The aim of the study was to identify people practising tracking (mantrailing) on the territory of Poland. The profile and motives for practicing mantrailing, determined on the basis of survey results, have been supplemented with definitions and the current state of knowledge on mantrailing. Attention was paid to the necessity of undertaking further research contributing to better knowledge and understanding of this dynamically developing form of recreation. The main motives for practicing mantrailing in Poland are to determine the needs and predispositions of a dog and the desire to learn about its features directly in the field work conditions. For amateurs of mantrailing, passing exams and obtaining certificates in this field is not crucial, neither is the aspect of competition between their dogs. They treat mantrailing as a year-round outdoor activity, in all field conditions. They practice it usually once a week, classifying it due to the intensity of the effort as medium intensive, and due to the level of technical complexity as medium difficult. The vast majority of people practicing mantrailing are physically fit and, as in most dog-related activities, the largest number of them are women. The list of mantrailing dog breeds is greatly diverse. In most opinions, there is also a lack of strong indications of the breeds preferred in mantrailing. The main inhibitors of this activity in Poland are time constraints and financial factors.